Penerapan Teknik Intervensi Gabungan Discrete Trial Training dan Pivotal Response Training untuk Meningkatkan Keterampilan Joint Attention pada Anak dengan Autism Spectrum Disorder - Fitriany Juhari; Rini Hildayani; Eko Handayani (Humanitas (Jurnal Psikologi), 2025)
Deficit in joint attention is one of characteristics children with autism spectrum disorder (ASD), and a skill researchers have identified it as foundational to child development. JA is intrinsically linked to the development of language and social interaction skills in both typically developing children and those with ASD. Consequently, experts advocate for joint attention to be a primary target in intervention programs for children with autism. In the present study, JA skills were cultivated in children with ASD using a blended intervention model that combines discrete trial training (DTT) and pivotal response training (PRT), both of which are rooted in the behavioral approach. The intervention specifically targeted two facets of JA: responding to joint attention (RJA) and initiating joint attention (IJA). The findings indicated that the combined DTT and PRT intervention effectively enhanced both RJA and IJA skills in the participating children with ASD. These results suggest that aptly combined, behaviorally-based interventions can yield positive outcomes in improving core developmental functions in this population. Furthermore, this study underscores the critical importance of early detection and intervention, as well as the development of individualized therapeutic programs that target key social skills such as joint attention. Based on these positive outcomes, the integrated DTT and PRT approach warrants consistent consideration as a viable strategy, particularly for enhancing the core developmental capacities of children with ASD.